Identification of an allosteric binding site for RORγt inhibition - Scheepstra, Marcel; Leysen, Seppe; van Almen, Geert C.; Miller, J. Richard; Piesvaux, Jennifer; Kutilek, Victoria; van Eenennaam, Hans; Zhang, Hongjun; Barr, Kenneth; Nagpal, Sunil; Soisson, Stephen M.; Kornienko, Maria; et al. (Nature communications, 2015)
RORγt is critical for the differentiation and proliferation of Th17 cells associated with several chronic autoimmune diseases. We report the discovery of a novel allosteric binding site on the nuclear receptor RORγt. Co-crystallization of the ligand binding domain (LBD) of RORγt with a series of small-molecule antagonists demonstrates occupancy of a previously unreported allosteric binding pocket. Binding at this non-canonical site induces an unprecedented conformational reorientation of helix 12 in the RORγt LBD, which blocks cofactor binding. The functional consequence of this allosteric ligand-mediated conformation is inhibition of function as evidenced by both biochemical and cellular studies. RORγt function is thus antagonized in a manner molecularly distinct from that of previously described orthosteric RORγt ligands. This brings forward an approach to target RORγt for the treatment of Th17-mediated autoimmune diseases. The elucidation of an unprecedented modality of pharmacological antagonism establishes a mechanism for modulation of nuclear receptors. Upon the binding of small ligands, nuclear receptors regulate the transcription of genes that are associated with a number of disease mechanisms. Here, the authors report on a novel allosteric ligand binding site on the nuclear receptor RORγt.